2011
DOI: 10.1111/j.1399-0004.2011.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behavior of individuals with increased risk of having a child with retinoblastoma

Abstract: To investigate reproductive behavior of individuals at increased risk of having a child with retinoblastoma (Rb), we conducted a cross-sectional questionnaire survey among 118 counselees visiting the Clinical Genetics Department of the National Rb Center in the Netherlands. The recurrence risk for counselees ranged from <1% to 50%. The response rate was 69%. Of 43 respondents considering having children after becoming aware of their increased risk, Rb influenced reproductive behavior for 25 (58%), of whom 14 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Furthermore, appropriate counselling about reproductive options can be provided to RB1 carriers and parents of children with Rb. As we have shown in previous studies, reproductive behaviour is influenced by Rb for many parents at increased risk for a child with Rb 8 9. Several patients with Rb in our cohort were unaware of the hereditary nature of their disease and conceived children who developed Rb and were not screened from birth, nor had the parents had the opportunity to consider other reproductive options, for example, prenatal diagnosis or preimplantation genetic diagnosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, appropriate counselling about reproductive options can be provided to RB1 carriers and parents of children with Rb. As we have shown in previous studies, reproductive behaviour is influenced by Rb for many parents at increased risk for a child with Rb 8 9. Several patients with Rb in our cohort were unaware of the hereditary nature of their disease and conceived children who developed Rb and were not screened from birth, nor had the parents had the opportunity to consider other reproductive options, for example, prenatal diagnosis or preimplantation genetic diagnosis.…”
Section: Discussionmentioning
confidence: 78%
“…These eye exams would no longer be necessary if an increased risk could be excluded through DNA testing. Furthermore, knowledge of the presence of an RB1 mutation in the germline, or two RB1 mutations in the Rb tumour and none in the germline, can aid families in reproductive decision making,8 9 emphasising the clinical importance for RB1 mutation scanning.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to increased worry influencing reproductive behavior, as reported in smaller studies of RB survivors. 7,11 Our findings characterize RB survivors as a fairly healthy and resilient group but highlight some potential areas for future research and clinical counseling. Although RB survivors were coping well, survivors of bilateral disease endorsed greater fears of recurrence or second malignant neoplasms as well as fears of passing RB to their children, perhaps highlighting a greater need for long-term psychosocial and genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Survivors' reproductive behaviors have also been influenced by the perceived risk of having a child with RB. [7][8][9][10][11][12][13] However, interpretation of these studies has generally been limited by small sample sizes and lack of comparison populations.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on reproductive decisions of couples at risk of having a child with retinoblastoma (Rb), a rare type of eye cancer in early childhood [3, 4]. Several couples who participated in these studies reported that they had chosen PND to prevent the birth of an affected child with Rb.…”
Section: Introductionmentioning
confidence: 99%